Risk of gestational hypertension and preeclampsia in pregnant women with new onset blood pressure of 120-129/≤89 mmHg: a meta-analysis of prospective studies - Yun Liu; Qingfang Meng (Taylor & Francis Group, 2022)
Background To explore whether elevated blood pressure and stage 1 hypertension were risks to GH and PE occurrence by a meta-analysis. Methods Electronic databases were searched systematically up to Dec 2020. Combined risk ratio (RR) and 95%CI were used to evaluate the relationship between two blood pressure groups and GH and PE. Results Seven studies were included in this study. In elevated blood pressure group, the overall RR of GH group is 1.93 and the combined RR is 1.98 in PE group. Conclusion Elevated BP and stage 1 hypertension were risk factors of GH and PE occurrence in pregnant women.